2017
DOI: 10.1002/jclp.22474
|View full text |Cite
|
Sign up to set email alerts
|

The Existential Concerns Questionnaire (ECQ)–Development and Initial Validation of a New Existential Anxiety Scale in a Nonclinical and Clinical Sample

Abstract: Initial results regarding the psychometric properties of the ECQ are promising.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
37
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(37 citation statements)
references
References 31 publications
0
37
0
Order By: Relevance
“…Many patients diagnosed with cancer identify as neither religious nor spiritual but clearly have existential if not religious and/or spiritual issues. For these patients, the revised guidelines include existential items representing themes found in the Existential Distress Scale (feelings of worthlessness and loneliness 33 ) and Existential Concerns Questionnaire (concerns about dying/death and/or afterlife 34 ). Clearly these additional 3 items are concerns that could be experienced by anyone regardless of religious and/or spiritual identity.…”
Section: Newly Integrated Revisions To the Chaplaincy Section Of The mentioning
confidence: 99%
“…Many patients diagnosed with cancer identify as neither religious nor spiritual but clearly have existential if not religious and/or spiritual issues. For these patients, the revised guidelines include existential items representing themes found in the Existential Distress Scale (feelings of worthlessness and loneliness 33 ) and Existential Concerns Questionnaire (concerns about dying/death and/or afterlife 34 ). Clearly these additional 3 items are concerns that could be experienced by anyone regardless of religious and/or spiritual identity.…”
Section: Newly Integrated Revisions To the Chaplaincy Section Of The mentioning
confidence: 99%
“…Second, since no unified tool had been detected at the time of performing the study, different tools had been used for measuring each aspect of existential well-being. However, due to the recently developed Existential Concern Questionnaire (ECQ), 25 perhaps further research, using the ECQ, may reveal more novel findings.…”
Section: Limitations Of the Studymentioning
confidence: 99%
“…For example: the Existential Concerns Questionnaire (ECQ) 25 was proven to be valid and reliable for the general population and for people suffering from psychiatric disorders. In our present study, only part of the ECQ factors were examined (meaning, death anxiety), while others were not examined, since literature review reported other topics to be main sources for existential concern among people suffering from terminal illness (e.g., satisfaction with life).…”
Section: Limitations Of the Studymentioning
confidence: 99%
See 2 more Smart Citations